Efficacy of Liraglutide: GLP 1 Receptor Agonist on Glycemic Control and Weight Loss among Patients with Type 2 Diabetes - Fatima Jehangir; Noor Rahman; Fatema Ropani; Tariq Adnan (ziauddin University, 2020)
Background: American Diabetes Association (ADA) made conspicuous changes in its 2019 Standards of Care Diabetes guidelines by choosing Glucagon like Peptide 1 (GLP1) receptor agonists and Sodium Glucose co-transporter 2 (SGLT2) inhibitors as the second line treatment options after metformin because both classes of drugs are cardiovascular friendly as proved in the Cardiovascular Outcome Trials (CVOT). GLP analogs show massive weight loss benefits apart from offering good glycemic control. We aimed to determine the impact of liraglutide on correction of hyperglycemia and body weight in Asian population. Methods: A cross sectional pre-post observational study enrolling 49 Type 2 diabetic patients with uncontrolled blood glucose, 15 years and above who agreed to use liraglutide apart from standard care, for glycemic control were recruited in the study. Study site was general practice clinic in Clifton and family medicine health care center Ziauddin University. Pre and post treatment HbA1C and BMI were observed after adding on Liraglutide 1.8 mg to metformin 1 gm bid, over a period of 12 weeks. Differences in the changes in BMI and HbA1C were examined using McNemar's test. Results: Mean age of the participants was 44.4 years. Duration of Diabetes was 65.1 months i.e. 5.4 years. At week 12, liraglutide 1.8 mg significantly reduced HbA1C levels by 0.94% (8.53+1.07 vs. 7.56+1.04 p-value <0.05) and BMI by 6.2kg (37.23+ 5.3 vs. 31.27.6+5.5 p-value <0.05) statistically significant. Conclusion: Liraglutide 1.8 mg over a period of 12 weeks, significantly reduced body weight (6.2kg p-value 0.05) and improved glycemic control (0.94% p-value<0.05) without causing hypoglycemia.